Caracterização de íons solúveis em água presentes no material particulado atmosférico PM10 amostrados na aduana da Ponte da Amizade, Foz do Iguaçu - PR - Silva, Willian Bogler da (2019)
Gases and particulate materials are among the main atmospheric pollutants, and depending on the concentration found, negatively impact the environment. Particularly among the main pollutants are particulate materials, which are structures of varying sizes, with solid or liquid characteristics which, in diameters of less than 10 micrometers, are easily inhalable. The objective of the present work was to characterize and quantify the chemical composition of water soluble major inorganic ions associated with PM10inhalable particulate matter in the Customsregion of Ponte da Friendship, Foz do Iguaçu, PR. The ions determined were Cl-, NO3-, SO42-, Na+, K+, NH4+, Mg2+Ca2+. The sampling methodology, sample preparation and analysis consisted of the sampling of atmospheric particulate matter with a diameter of 10 μm in two campaigns, March and August 2018, in quartz filters coupled to a large volume Hi-vol sampler, which operated in continuous flow for 24 hours, followed by 24 hours of inoperation, at which time there were filter changes and storage on parchment paper, which was inserted in Ziplock plastic packaging. The sample preparation procedure consisted of fragmentation of the filters into 4.4 cm diameter discs and accommodation in polyethylene bottles with 20 mLof ultrapure water and then mechanical stirring for 1 min and subsequent bathing. 12 h ultrasonic filtration by Nylon membrane and 0.025 liters with ultrapure water. The determination of Cl-, NO3-, SO42-and NH4+was made by ion chromatography. For K+, Mg2+, Na+and Ca2+, atomic absorption spectrometry was used. For the first campaign, 190 ± 111 ng m3for Cl-, 850 ± 61.2 ng m3for NO3-, 1226 ± 82.3 ng m3for SO42-, 147 ± 88.9 ng m3for Na+, 254 were measured. ± 165 ng m3for K+, 427 ± 204 ng m3for Mg2+, 145 ± 72.3 for Ca2+and 79.6 ± 43.3 ng m3for NH4+. In the second campaign, 61.0 ± 47.0 ng m3for Cl-, 252 ± 82.2 ng m3for NO3-, 450± 9.55 ng m3for SO42-, 58.0 ± 38.0 ng m3were measured for Na+, 116 ± 75.5 ng m3for K+, 172 ± 87.7 ng m3for Mg2+, 34.7 ± 28.0 ng m3 for Ca2+and 51.0 ± 29.6 ng m3for NH4+. These values were submitted to statistical tests, which validated the interference of seasonality on the concentration of 6ions, they are: Cl-,NO3-, SO42-,Na+,Mg2+e Ca2+. The K+and NH4+did not show statistical changes in concentration with seasonality. Through a specific program, he found possible atmospheric particulate material discharges, also from international areas, presenting several sources of contribution, such as the crust, oceans, forests, plantations, industries and other anthropogenic sources.